2019
DOI: 10.1111/iwj.13189
|View full text |Cite
|
Sign up to set email alerts
|

Systemic translation of locally infiltrated epidermal growth factor in diabetic lower extremity wounds

Abstract: Diabetic foot ulcer is one of the most frightened diabetic complications leading to amputation disability and early mortality. Diabetic wounds exhibit a complex networking of inflammatory cytokines, local proteases, and reactive oxygen and nitrogen species as a pathogenic polymicrobial biofilm, overall contributing to wound chronification and host homeostasis imbalance. Intralesional infiltration of epidermal growth factor (EGF) has emerged as a therapeutic alternative to diabetic wound healing, reaching respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…Our study showed that fibroblasts, particularly DFU-derived ones, not only act as sentinel cells, 57 but also respond to therapeutic stimuli such as EGF, by decreasing the aberrant activation of the TLR signalling pathways and, consequently, the levels of inflammatory mediators. These results contribute to explain our previous in vivo observations about the reduction of circulating levels of inflammatory cytokines after local administration of human recombinant EGF in DFU, 18 which stimulate granulation and wound closure in diabetic patients.…”
Section: Discussionsupporting
confidence: 80%
“…Our study showed that fibroblasts, particularly DFU-derived ones, not only act as sentinel cells, 57 but also respond to therapeutic stimuli such as EGF, by decreasing the aberrant activation of the TLR signalling pathways and, consequently, the levels of inflammatory mediators. These results contribute to explain our previous in vivo observations about the reduction of circulating levels of inflammatory cytokines after local administration of human recombinant EGF in DFU, 18 which stimulate granulation and wound closure in diabetic patients.…”
Section: Discussionsupporting
confidence: 80%
“…This was the fi rst clinical validation of in vitro and animal data indicating that EGF's cytoprotective eff ect is at least partially mediated by correcting the redox balance. [18,73,[76][77][78] A more recent study by García-Ojalvo and colleagues [79] confi rmed previous observations concerning the systemic impact of locally-infi ltrated EGF on reestablishment of a physiological redox balance. Moreover, the new data indicates that EGF's eff ect extends to reduction of diabetic endovascular pro-infl ammatory markers.…”
Section: Special Articlesupporting
confidence: 58%
“…Furthermore, EGF may have inhibitory effects on melanogenesis by reduction of inflammation and promotion of effects on the regeneration of the epidermal barrier in damaged tissues [33,34]. The antioxidant effect of EGF could also induce anti-melanogenesis [16,35]. However, there are few clinical studies evaluating the anti-pigmentation effect of EGF on pigmentary disorders [12].…”
Section: Discussionmentioning
confidence: 99%
“…In actual practice, EGF is commonly used to treat chronic skin ulcers, including diabetic foot ulcers and burn injuries [14,15]. It has been reported that EGF has anti-inflammatory and antioxidant effects and directly lowers melanin production [12,13,16]. Based on this action, the possibility of the applicability of EGF on antipigmentation has recently been proposed.…”
Section: Introductionmentioning
confidence: 99%